Methods of formation of lexicology in hindi language. - Kokeyeva., D. M.; Shorabek., G. A. (Journal of Oriental Studies, 2016)
This article explains change of religion, including Islam in historical and philosophical context. Also carefully analyzed the lexicological changes that have resulted from the influence of modern processes of language.